Respon Fisiologis Varietas Bawang Merah Dataran Rendah Terhadap Intensitas Naungan Agroekosistem Karawang - Dini Yuandini; Miftakhul Bakhrir Rozaq Khamid; Devie Rienzani Supriadi (Jurnal Agrosains dan Teknologi, 2026)
Shallot (Allium ascalonicum L.) is a high-value horticultural crop whose productivity is strongly influenced by light intensity, particularly in lowland agroecosystems such as Karawang characterized by high temperature and solar radiation. This study aimed to evaluate the physiological responses of several shallot varieties under different shading levels. The experiment was conducted using a Split Plot Design with two factors: shading intensity (0%, 40%, and 65%) and varieties (Bima Brebes, Bauji, and Tajuk). Observed parameters included leaf color, chlorophyll content (SPAD), leaf area, leaf area index, fresh and dry leaf weight, root length, transpiration rate, and relative water content (RWC). The results showed significant interaction between shading and variety on leaf color and chlorophyll content at several observation stages. Increasing shading intensity significantly reduced SPAD values in Bima Brebes and Tajuk, while Bauji exhibited greater chlorophyll stability under shaded conditions. Shading reduced photosynthetic efficiency due to limited light availability, leading to lower biomass accumulation. In contrast, no shading resulted in the highest chlorophyll content, particularly in the Tajuk variety. This study concludes that physiological responses of shallot are influenced by genotype–environment interaction, with no shading providing the most optimal physiological performance.